2020
DOI: 10.1038/s41598-020-66116-4
|View full text |Cite
|
Sign up to set email alerts
|

A Unique Mouse Model of Early Life Exercise Enables Hippocampal Memory and Synaptic Plasticity

Abstract: physical exercise is a powerful modulator of learning and memory. Mechanisms underlying the cognitive benefits of exercise are well documented in adult rodents. Exercise studies targeting postnatal periods of hippocampal maturation (specifically targeting periods of synaptic reorganization and plasticity) are lacking. We characterize a model of early-life exercise (ELE) in male and female mice designed with the goal of identifying critical periods by which exercise may have a lasting impact on hippocampal memo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 65 publications
3
25
0
1
Order By: Relevance
“…Evidence from animal studies also supports that exercise can enhance brain plasticity. Moderate-intensity aerobic exercise promotes the proliferation and survival of neurons in the hippocampus and cortex, increased BDNF and dendrites, and improves spatial learning and memory in rodents ( Serra et al, 2019 ; Ivy et al, 2020 ). Another study also reported that moderate-intensity swimming training could ameliorate the anxiety-like behavior of mice by increasing proteins that play a key role in hippocampal plasticity, such as growth-associated protein 43, synaptophysin, and BDNF ( Liu et al, 2018 ).…”
Section: Main Textmentioning
confidence: 99%
“…Evidence from animal studies also supports that exercise can enhance brain plasticity. Moderate-intensity aerobic exercise promotes the proliferation and survival of neurons in the hippocampus and cortex, increased BDNF and dendrites, and improves spatial learning and memory in rodents ( Serra et al, 2019 ; Ivy et al, 2020 ). Another study also reported that moderate-intensity swimming training could ameliorate the anxiety-like behavior of mice by increasing proteins that play a key role in hippocampal plasticity, such as growth-associated protein 43, synaptophysin, and BDNF ( Liu et al, 2018 ).…”
Section: Main Textmentioning
confidence: 99%
“…Aerobic exercise has generally been found to enhance performance on cognitive tasks involving the hippocampus in both adult humans and animal models 15,16 . The type, timing, and duration of exercise exposure matters with regard to whether it has a persistent impact on hippocampal function [17][18][19] . However, in general, the effects of exercise on hippocampal memory in adulthood are transient [17][18][19] .…”
Section: Introductionmentioning
confidence: 99%
“…The type, timing, and duration of exercise exposure matters with regard to whether it has a persistent impact on hippocampal function [17][18][19] . However, in general, the effects of exercise on hippocampal memory in adulthood are transient [17][18][19] . Findings in adult rodents also implicate a role for histone modifying enzymes in the mechanisms of exerciseinduced benefits to hippocampal memory.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations